Patterns of pre-donation deferral in voluntary blood donors with its impact on the donor pool- A study in a tertiary care hospital - Dr. Reshma Anegundi; Dr. Divyashree B N (Tropical Journal of Pathology and Microbiology, 2021)
Background: The prime responsibility of a Blood Transfusion Service is to provide a very safe, sufficient and timely supply of blood and its components to those in need. In fulfilling this responsibility, the Blood Transfusion Service should ensure that the act of blood donation is safe and causes no harm to the donor. Aims and objectives: To estimate the incidence of pre-donation deferral in a tertiary care institute and to estimate various factors for donor deferral.Material and methodology: A retrospective analysis of donors data was collected from January 2019 to December 2019 from the donor deferral registry maintained in the blood bank. In this study, the subjects who visited our blood bank or arrived at a voluntary blood donation camp for purpose of donating blood were screened by donor questionnaire and basic physical examination done with recording vital signs(temperature, blood pressure, pulse rate) followed by hemoglobin estimation and blood grouping.Results: In the present study, 456 donors were deferred from donation. The deferral rate was 13.6%. Deferral rate was high among males. The majority of deferrals, were temporary deferrals, 380(83.33%) and 76(16.66%) were permanent deferrals. Anemia was the most common cause among temporary deferrals constituting 56.05% of temporary deferrals and 46.71% of total deferrals.Conclusion: Attempts should be made to create awareness among potential donors by conducting health talks, distributing educational pamphlets, counselling donors during donation and encouraging them for future donations.